(untitled) (Eurasian Research Bulletin, 2025)
The methodology for using artificial intelligence systems to achieve sustainable economic growth is an integral part of the modern digital economy. The article analyzes the impact of artificial intelligence technologies on economic processes, the methodological foundations for their effective implementation in management, production, financial and tax systems. It also highlights the possibilities of rational use of economic resources, increasing labor productivity and strengthening competitiveness with the help of artificial intelligence. The experience of foreign countries and the advantages and problems of implementing AI systems in the conditions of the economy of Uzbekistan are analyzed. The results of the study show that management approaches based on artificial intelligence are an important factor in achieving sustainable economic growth and increasing efficiency.